2010
DOI: 10.1096/fj.10-166884
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin‐dependent activation of the epithelial calcium‐dependent chloride channel TMEM16A

Abstract: TMEM16A (anoctamin 1, Ano1), a member of a family of 10 homologous proteins, has been shown to form an essential component of Ca2+‐activated CU channels. TMEM16A‐null mice exhibit severe defects in epithelial transport along with tracheomalacia and death within 1 mo after birth. Despite its outstanding physiological significance, the mechanisms for activation of TMEM16A remain obscure. TMEM16A is activated on increase in intracellular Ca2+, but it is unclear whether Ca2+ binds directly to the channel or whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
183
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(203 citation statements)
references
References 58 publications
15
183
4
Order By: Relevance
“…Additionally, whether TMEM16A binds Ca 2+ -CaM is controversial-some biochemical pull-down studies support an interaction (31,32), whereas others do not (40). Notably, pull-down methods can be notoriously inconsistent with regards to confirming apoCaM/Ca 2+ -CaM association with ion channels even when these are functionally known to occur (35,41).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, whether TMEM16A binds Ca 2+ -CaM is controversial-some biochemical pull-down studies support an interaction (31,32), whereas others do not (40). Notably, pull-down methods can be notoriously inconsistent with regards to confirming apoCaM/Ca 2+ -CaM association with ion channels even when these are functionally known to occur (35,41).…”
Section: Resultsmentioning
confidence: 99%
“…The actin cytoskeleton and its associated regulatory proteins could be implicated in Ano1 function by modulating Ano1 channel gating, directing the trafficking Ano1 to the apical membrane, or assembling Ano1 into signaling networks. It has been reported that both depolymerization of the actin cytoskeleton with cytochalasin-D and stabilization of the actin network with phalloidin suppresses Ano1 currents (42). A number of ion channels have been shown to interact with the actin cytoskeleton (43).…”
Section: Discussionmentioning
confidence: 99%
“…45 They show outward-rectification and a similar permeability sequence as described for VRAC (SCN ->I ->NO 3 ->Br ->Cl ->gluconate), they are activated by osmotic cell swelling in the presence of extracellular Ca 2C40 and requires cellular ATP. 22,43,44,46 However, VRAC and ANO1/6 activities can be distinguished by (i) their sensitivity to strongly buffered intracellular Ca 2C , i.e. VRAC can be activated whereas ANO1 cannot, (ii) activation/deactivation at positive potentials, i.e., VRAC deactivates 9,41,47 whereas ANO1/6 activates ( Fig.…”
Section: Biophysical Characterization Of Vracmentioning
confidence: 99%
“…126 Two putative CaM binding sites were identified on ANO1, which led to the proposal that Ca 2C sensitivity is mediated by calmodulin. 46,127 Recent papers did however present strong evidence against the possible role of calmodulin. 128,129 The most direct evidence that the Ca 2C sensitivity is intrinsic and not dependent on calmodulin comes from the observation that purified ANO1 reconstituted in liposomes recapitulates the functional properties of ANO1.…”
Section: Anoctamin1 -Ano1mentioning
confidence: 99%